Reshaping ties to land: a systematic review of the psychosocial and cultural impacts of Pacific climate-related mobility. (16th March 2022) - Yates, Olivia E. T.; Manuela, Sam; Neef, Andreas; Groot, Shiloh
ABSTRACT: Global inaction on climate change is leading many Pacific peoples towards a reality separated from their ancestral lands. Yet, discussions of climate-related mobility often sideline Pacific understandings of well-being. This systematic qualitative review synthesizes the literature on the psychosocial and cultural impacts of climate-related mobility in the Pacific and outlines the methods employed in this field. We identified 36 relevant empirical studies from online databases and citations covering 28 cases of climate-related mobility. Our approach assessed studies against the Pacific Health Research Guidelines and the Critical Appraisal Skills Programme. We conducted a thematic synthesis of qualitative findings, recognizing social factors influencing acculturation and relationship to land as superordinate themes for both cross-border and internal mobility. Eleven sub-themes were identified as outcomes of cross-border and internal mobility. Overall, climate-related mobility shifted people's relationships with their homelands, disrupting community and cultural continuities. People resisted disruptions through engaging with cultural practices, values, knowledge, and community life. Yet, even the least disruptive movements caused significant stress, suggesting that Pacific conceptualisations of well-being and land should be considered when developing climate policy.